The Role of Zakat to Support Regional Fiscal Independence - Yuletri, Masni; Iska, Syukri; Almasah, Munifah Zuhra; Wahyuni, Elmiliyani (Jurnal Iqtisaduna, 2025)
Most regions in Indonesia, including Tanah Datar Regency, still face challenges in achieving fiscal independence, reflected in the low ratio of local revenue to total revenue. This study aims to analyze the role of zakat as a strategic instrument in supporting regional fiscal independence, using data from the financial statements of the Regional Government and BAZNAS of Tanah Datar Regency in 2019-2023. The results showed that: (1) Tanah Datar Regency is categorized as “Not Independent” with an Index of Fiscal Independence (IKF) <0.25; (2) the realization of zakat in nominal terms is quite large and has the potential to reduce fiscal dependence on the Central Government; (3) zakat contributes to strengthening regional fiscal independence. This study concludes a positive relationship between zakat realization and fiscal independence and confirms that zakat can be one of the practical Islamic economic approaches in strengthening regional fiscal capacity.